Bacterial uropathogens and burden of antimicrobial resistance pattern in urine specimens referred to Ethiopian Public Health Institute. - Tesfa Addis (Public Library of Science (PLoS), 2021)
Background Urinary tract infections (UTIs) are the leading causes of morbidity in the general population, and is the second most common infectious disease after respiratory infections. Appropriate antibiotic therapy is essential to achieving good therapeutic results. Therefore, the purpose of this study was to investigate the profile of pathogens cultured from urinary tract infections and to determine their resistance profiles to commonly prescribed antibiotics. Method A cross-sectional study was carried out at the National Referral Laboratory of the Ethiopian Institute of Public Health from January 2017 to December 2018. All positive cultures were characterized by colony morphology, Gram stain, and standard biochemical tests. The antimicrobial susceptibility test of the isolate was performed using the Kirby- Bauer disk diffusion test on Muller-Hinton agar. In addition, bacterial identification, antimicrobial susceptibility testing and phenotypic detection of MDR were performed with VITEK 2 Compact according to the manufacturer's instructions. Result Out of 1012 cultured urine specimens, 325 (32.1%) was showed significant bacteriuria. The overall prevalence of UTIs was 325(32.1%) and the highest prevalence rate was obtained from 21-30 years age group 73(22.5%). Among UTIs patients, 583(57.6%) were females and 429(42.4%) were males. The UTIs of 179 (55%) women is relatively higher than that of men 146 (45%). Among 325 isolates, Gram-negative bacteria (GNB) appeared more frequently 252 (51.7%) than Gram-positive bacteria 63 (19.4%). In GNB, E. coli 168(66.7%), Klebsiella species 32(12.7%), and Enterobacter species 13 (5.2%) were dominated isolates whereas in GPB accounted for coagulase-negative staphylococcus (CoNS) 33(52.4%), Enterococcus species 16(25.4%), and Staphylococcus aureus 10(15.9%). Major of the isolates showed high levels of antibiotic resistance to commonly prescribed antimicrobials. Imipenem, Amikacin, and Nitrofurantoin were the most sensitive antibiotics for Gram-negative isolates while Nitrofurantoin, clindamycin, and Gentamycin were effective against gram-positive uropathogens. Overall, 156/256(60.9%), 56/256(22.4%), 10/256(4%) of gram-negative isolates were MDR, XDR, and PDR respectively while among the GPB isolates, 34/63(53.1%), 10/63(15.8%), and 1/63(1.6%) were MDR, XDR, and PDR isolates respectively. Among the tested bacterial strains, 190/319 (59.5%) were MDR, 66/319 (20.7%) strains were XDR, and 11/319 (3.45%) were PDR isolated. Conclusion The prevalence of urinary tract infection was high, and Gram-negative organisms were the most common causes of UTIs in this study. It was found that the resistance to commonly used antibiotics is very high. Early detection and close monitoring of MDR, XDR, or even PDR bacterial strains must be started by all clinical microbiology laboratories to reduce the menace of antimicrobial resistance that is now a global problem.